Nucleic acid-based therapeutics for the treatment of central nervous system disorders - McCartan, Robyn; Khorkova, Olga; Volmar, Claude-Henry; Wahlestedt, Claes (Frontiers in Genetics, 2023)
Nucleic acid-based therapeutics (NBTs) are an emerging class of drugs with potential for the treatment of a wide range of central nervous system conditions. To date, pertaining to CNS indications, there are two commercially available NBTs and a large number of ongoing clinical trials. However, these NBTs are applied directly to the brain due to very low blood brain barrier permeability. In this review, we outline recent advances in chemical modifications of NBTs and NBT delivery techniques intended to promote brain exposure, efficacy, and possible future systemic application.